Thermophysical properties charaterisation of water based mango oxide hybrid nanofluid - James Lau, Tze Chen (2020)
Nanofluid can be described as a mixture of nanoparticles and base fluid. Many researchers attempted to enhance the thermal conductivity of base fluids by adding metallic and non-metallic nanoparticles in fluids. Although metallic and non-metallic nanoparticles can increase the thermal conductivity of base fluids, it also increases the viscosity of base fluids that causes a high pressure drop in the heat transfer application. This results that higher pumping power is needed which in turn increases the system operation cost. Therefore, an alternative solution needs to be devised. For this, hybrid nanofluid with a combination of metallic or non-metallic nanoparticles and bio nanoparticles dispersed in a base fluid can be one option to reduce the pressure drop further while maintaining the heat transfer application. This is because of the addition of bio nanoparticles that have fibre by nature in fluids resulting in low thermal conductivity enhancement with an exponentially decreasing trend of viscosity that might reduce pressure drop. Thus, the three objectives of this research are to determine the stability of mango/oxide hybrid nanofluid, to evaluate thermophysical properties of mango/oxide hybrid nanofluid and to measure the optimum parameters for enhanced thermal properties and reduced viscosity. Mango bark (MB) and mango leaf (ML) nanoparticles were first produced using the top-down method. In the second processing step, the MB and ML nanoparticles that are prepared separately mixed with oxide nanoparticles and suspended into the base fluid using stirrer and an ultrasonic bath. Stability of the nanofluids was measured using sedimentation method and UV-Vis analysis. Then, density, viscosity, thermal conductivity and specific heat capacity of the nanofluids were evaluated using theoretical and experimental method. After that, the optimum parameters for enhanced thermal properties and reduced viscosity of nanofluids were determined using Response Surface Methodology (RSM). From the results, the nanofluids have stability in moderation with the sign of sedimentation after 1 day and slightly increased after 14 days. All nanofluids are stable and applicable at 300nm wavelength with average peak absorbance of 2.491. At 30oC with 1% of volume concentration, MB/TiO2 and ML/TiO2 water-based nanofluids have 12.2% and 14.7% reduced viscosity than TiO2 water-based nanofluid. MB/SiO2 and ML/SiO2 water-based nanofluids have 3.2% and 4.4% reduced viscosity than SiO2 water-based nanofluid. At 30oC with 1% of volume concentration, MB/TiO2 and ML/TiO2 water-based nanofluids have maintained thermal conductivity enhancement with 4.5% and 5.4% lower than TiO2 water-based nanofluid. MB/SiO2 and ML/SiO2 water-based nanofluids have maintained thermal conductivity enhancement with 1.1% and 1.6% lower than SiO2 water-based nanofluid. Density and specific heat capacity are dependent on the material type. The viscosity decreased with temperature and increased with concentration. Meanwhile, the thermal conductivity increased with temperature and concentration. From the results of RSM, MB/oxide nanofluids have the most enhanced thermal conductivity and reduced viscosity with the material type of MB/SiO2 (12.92% SiO2 and 87.08% of mango bark), the temperature of 70oC and concentration of 0.25. Meanwhile, ML/oxide nanofluid have the most enhanced thermal conductivity and reduced viscosity with the material type of MB/SiO2 (42.98% SiO2 and 57.02% of mango leaf), the temperature of 70oC and concentration of 0.25%. In conclusion, mango/oxide hybrid nanofluids have stability in moderation with reduced viscosity and maintained thermal conductivity enhancement than non-bio based nanofluids that can be used to reduce the pressure drop further while maintaining the heat transfer application.